Determinants of foreign direct investment in Malaysia / Farah Wahida Abd Rahim - Abd Rahim, Farah Wahida (Faculty of Business and Management, 2019)
The purpose of this study is to examine the determinants of foreign direct investment in Malaysia. The determinants are inflation rate (IR), gross domestic product (GDP), exchange rate (ER) and trade openness (TRO). The study was using time series data from 1980 to 2017 by using yearly data. Multiple linear regression test has been used in this study. The result shows that inflation rate and gross domestic product have positive and significant relationship towards foreign direct investment in Malaysia. Meanwhile, there is insignificant relationship between exchange rate and trade openness on foreign direct investment in Malaysia. It means exchange rate and trade openness has no significant effect on Foreign direct investment in Malaysia.